2020
DOI: 10.1097/scs.0000000000006750
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Glenoid Fossa Morphology Between Different Sagittal Skeletal Pattern Using Cone Beam Computed Tomography

Abstract: Morphology of glenoid fossa might help the clinician in the diagnosis, establishing more biological treatment modalities and treatment response between patients with different skeletal malocclusions. This study aimed to assess the glenoid fossa morphology in different sagittal facial types using CBCT. The CBCT images of 64 patients with normal vertical growth patterns were classified into class I, class II, and class III based on the skeletal sagittal analysis. Depth, width, and angle of glenoid fossa were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…Importance of glenoid fossa must be acknowledged in shaping craniofacial anatomy of skeletal Class-I, Class-II and GF location must be looked before making the treatment plan of these skeletal malocclusions. 12 In our study 36(60%) girls and 24(40%) boys were present. This difference of gender in our study was because of small sample size, more adolescent female patients under treatment between age group of 10-12 years.…”
Section: Discussionsupporting
confidence: 50%
“…Importance of glenoid fossa must be acknowledged in shaping craniofacial anatomy of skeletal Class-I, Class-II and GF location must be looked before making the treatment plan of these skeletal malocclusions. 12 In our study 36(60%) girls and 24(40%) boys were present. This difference of gender in our study was because of small sample size, more adolescent female patients under treatment between age group of 10-12 years.…”
Section: Discussionsupporting
confidence: 50%
“…One study showed larger values of the glenoid fossa height compared with skeletal class II [55]. Two other studies stated that the widest glenoid fossa is commonly seen in skeletal class I [59,61] .…”
Section: Tmj Articular Eminence and Mandibular Fossa Inmentioning
confidence: 99%
“…Of the papers included in the systematic review, 15 articles investigated the correlation of joint eminence/fossa features, as assessed by CBCT, with maxillofacial morphology and malocclusion. These papers were published between 2013 and 2021 and focused on populations from China [22,46,59], Brazil [35,40], Peru [34], South Korea [24,54,55], Egypt [56,57], Turkey [51], India [49], Italy [60], and Iran [61]. Sample sizes ranged from 28 [51] to 213 [40] patients.…”
Section: Tmj Articular Eminence and Mandibular Fossa In Cbctmentioning
confidence: 99%
“…However, the most commonly cited method of investigating the mandible today is still 2D cephalometric radiograph-based superimposition [ 9 ]. There is no doubt that 2D image-projected 3D structure analysis not only limits the regions that can be evaluated (e.g., mandibular condyle [ 10 ], glenoid fossa [ 11 ], coronoid process, mandibular canal [ 12 ]), but also exposes the findings to inherent and unavoidable errors, such as those rooted in differences in magnification, head position, landmark identification, tracing, and reference lines and planes used for superimposition [ 13 ]. Thus, reliable 3D mandibular structure analysis technologies are in high demand, especially those that can provide valuable information previously inaccessible using 2D methods [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%